Benih dasar, benih sebar, Vima-1 EVALUASI PERTUMBUHAN DAN HASIL BEBERAPA GENERASI BENIH KACANG HIJAU (Vigna radiata L.) VARIETAS VIMA-1 DENGAN PERLAKUAN PENYIANGAN - Hasna, Ratu Nurul; Sudirman, Sudirman; Jaya, I Komang Damar (Department of Agronomy, Faculty of Agriculture, University of Mataram and Indonesian Society of Agronomy, NTB Branch, 2023)
This study aimed to determine the appropriate weeding time and its effect on growth and yield on several generations of mung bean seeds (Vigna radiata L.) planted in a dry land. A field trial was conducted from September to November 2018 in the hamlet of Amor-amor, Gumantar Village, Kayangan District, North Lombok Regency. The weeding times tested were: 2 weeks after planting, 4 weeks after planting and without weeding. Meanwhile, the seed generation factors were: foundation seeds, the first-generation of extension seeds and the second-generation of extension seeds. All the treatments were arranged factorially using a Randomized Block Design with 3 replications. The results showed that there was no interaction between weeding time and seed generation in affecting plant growth, but weeding time and seed generation affected crop yields. The highest yield of mung bean seeds was obtained from weeding treatment at 2 weeks after planting, while the seed generation that gave the highest yield was the second extension seeds. To grow mung beans of Vima-1 variety in dry lands, it is recommended to do weeding at 2 weeks after planting and to use the second generation of extension seeds.